Association between the extension of smoke-free legislation and incident acute myocardial infarctions in Singapore from 2010 to 2019: an interrupted time-series analysis - Joel Aik; Nan Liu; Huili Zheng; Eric Jou; Jamie S Y Ho; Andrew F W Ho (BMJ Global Health)
Background We examined the association between smoke-free laws implemented in the outdoors and the common areas of residential apartment blocks and reported acute myocardial infarctions (AMI) in Singapore.Methods We used an interrupted time-series design and seasonal autoregressive integrated moving average models to examine the effect of the smoke-free law extensions in 2013 (common areas of residential blocks, covered pedestrian linkways, overhead bridges and within 5 m of bus stops), 2016 (parks) and 2017 (educational institutions, buses and taxis) on the monthly incidence rate of AMIs per 1 000 000 population.Results We included 133 868 AMI reports from January 2010 to December 2019. Post-2013, there was a decrease in the AMI incidence trend (β=−0.6 per month, 95%CI −1.0 to –0.29) and 2097 (95% CI 2094 to 2100) more AMIs may have occurred without the extension. There was a significant step-decline in male AMIs and a non-significant step-increase in female AMIs post-2013. Those 65 years and older experienced a greater decline to the postlegislation 2013 trend (β=−5.9, 95% CI −8.7 to –3.1) compared with those younger (β=−0.4, 95% CI −0.6 to –0.2), while an estimated 19 591 (15 711 to 23472) additional AMI cases in those 65 years and above may have occurred without the extension. We found a step-increase in monthly AMI incidence post-2016 (β=14.2, 95%CI 3.3 to 25.0).Conclusion The 2013 smoke-free law extension to residential estates and other outdoor areas were associated with a decline in AMIs and those above the age of 65 years and men appeared to be major beneficiaries. Additional epidemiological evidence is required to support the expanded smoke-free legislation to parks, educational institutions, buses and taxis.